2022
DOI: 10.1101/2022.02.18.481041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Borrowing ecological theory to infer interactions between sensitive and resistant breast cancer cell populations

Abstract: While some forms of breast cancer are highly responsive to treatment, endocrine therapy-resistant breast cancers are disproportionately lethal. There has been significant progress in understanding how endocrine therapy-resistant strains evolve from therapy-susceptible strains of cancer, but little is understood about the proliferation of resistance through cancer cell populations or the interactions that occur between populations of resistant and sensitive cells. In this study, we characterize the nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Another predator-prey mathematical model showed evidence of reciprocal antagonism at play within competition dynamics of parental and radiation-resistant cell lines [24]. These models have also been applied to endocrine therapy [25] and doxorubicin therapy [26,27] in breast cancer cell lines. There is also evidence of the existence of positive or cooperative ecological interactions in cancer: one recent study indicated paracrine signaling as a mechanism for which the dominant cell line's growth is enhanced by the presence of a co-cultured second cell line [28].…”
Section: Measuring Effective Games In Oncologymentioning
confidence: 99%
“…Another predator-prey mathematical model showed evidence of reciprocal antagonism at play within competition dynamics of parental and radiation-resistant cell lines [24]. These models have also been applied to endocrine therapy [25] and doxorubicin therapy [26,27] in breast cancer cell lines. There is also evidence of the existence of positive or cooperative ecological interactions in cancer: one recent study indicated paracrine signaling as a mechanism for which the dominant cell line's growth is enhanced by the presence of a co-cultured second cell line [28].…”
Section: Measuring Effective Games In Oncologymentioning
confidence: 99%
“…cell density can either increase or decrease the efficacy of antibiotics. Existing work such as (Kaznatcheev et al 2019), (Paczkowski et al 2021), (Emond et al 2021), (Susswein et al 2022), and (Farrokhian et al 2022) shows that interactions between drug sensitive and resistant cancerous cells can shape the population’s evolution of drug resistance. To analyze the role of density dependence, especially in drug resistance, we consider one of the first, classical mathematical models of density-dependent population dynamics, Verhulst’s logistic growth model (Verhulst 1838), which describes the dynamics of a homogeneous population in terms of its net growth rate: …”
Section: Introductionmentioning
confidence: 99%
“…cell density can either increase or decrease the efficacy of antibiotics. Existing work such as (Kaznatcheev et al 2019), (Paczkowski et al 2021), (Emond et al 2021), (Susswein et al 2022), and (Farrokhian et al 2022) shows that interactions between drug sensitive and resistant cancerous cells can shape the population's evolution of drug resistance. To analyze the role of density dependence, especially in drug resistance, we consider one of the first, classical mathematical models of density-dependent population dynamics, Verhulst's logistic growth model (Verhulst 1838), which describes the dynamics of a homogeneous population in terms of its net growth rate:…”
Section: Introductionmentioning
confidence: 99%